Metaphor, the press, and the Canadian Security Intelligence Service (CSIS). - Tracey, Neil R. (University of Ottawa (Canada), 1990)
The dissemination of press information in areas of concern to criminal justice plays an important role in the public conceptions of crime and the criminal justice system. The theoretical basis of the work, which integrates studies in phenomenology and metaphor, serves as a vehicle to arrive at a critical understanding of the press portrayal of the security legislation (CSIS Act). The thesis studies press articles gathered from microfilms, government press clippings, and a computer search (Dialog, File 262) for the Vancouver Sun, Winnipeg Free Press, Toronto Globe and Mail, Toronto Star, Ottawa Citizen, Ottawa Le Droit, Montreal Gazette, Le Devoir. Specific sub-themes in the reporting of the CSIS indicate that: (1) the reporting was uniformly critical of the bill, (2) the issue of civil rights versus state security provided the boundaries of virtually all coverage, (3) the CSIS was consistently portrayed through totalitarian imagery. (Abstract shortened by UMI.)
Keywords: Sociology, Criminology and Penology.